Association of type ii diabetes mellitus with pulmonary tuberculosis: a clinical and radiological study - K, Jahnavi; Reddy C., Mallikarjuna; Madas, Swetha; Bindu M., Hima (International Journal of Advances in Medicine, 2017)
Background: The link between diabetes mellitus and tuberculosis has been recognized for centuries. It is only in the later years that the association has been identified. Diabetes mellitus has been reported to modify the presenting features of pulmonary tuberculosis, but there are varying data, particularly regarding the association with lower lung field involvement. Methods: 229 pulmonary/pleural fluid TB positive patients were tested for presence of type II diabetes. Clinical and radiological tests were done and analyzed for all patients. Results: 109 of 229 patients were diabetic and more than 50% of them were males. The most common symptoms were loss of appetite and weight, followed by cough and fever. Mixed zone involvement of the lung was a more common presentation than upper or lower zone. Conclusions: We have tried to highlight the importance of Diabetes mellitus as a potential risk factor for Pulmonary tuberculosis patients, especially in the geographical regions were the two diseases are highly prevalent. More studies need to be performed in a region to establish the association between the two.